Pullulanase modification of granular sweet potato starch: Assistant effect of dielectric barrier discharge plasma on multi-scale structure, physicochemical properties. (15th November 2021) - Ge, Xiangzhen; Shen, Huishan; Su, Chunyan; Zhang, Bo; Zhang, Qian; Jiang, Hao; Yuan, Li; Yu, Xiuzhu; Li, Wenhao
Abstract: This study explored the potential application of physical combined enzyme treatment to modify starch granules. Starch was modified by exposure to cold plasma (CP) for 1, 3, and 9 min and to pullulanase (PUL) for 12, 24, and 36 h. Individual treatments with CP and PUL somewhat modified starch structure and physicochemical properties. Nevertheless, compared with native starch and individual treatments, CP–PUL combined treatment significantly ( p < 0.05) promoted the subsequent structural modification, increased the short-chain ratio and the amylose content, reduce the molecular weight and the relative crystallinity, and disturb the short-range order. CP also improved the properties of PUL-modified starch, including enhanced solubility, thermal properties and resistance to enzymatic hydrolysis but worsened swelling power and peak viscosity properties. This research provides a new perspective for the rational application of CP–PUL co-treated starch in the food industry. Highlights: Cold plasma (CP) improved the pullulanase (PUL) modification efficiency of sweet potato starch. CP promoted the change of molecular and crystal structure in subsequent PUL. CP facilitated the improvement of physicochemical properties of the starch in subsequent PUL. Combined modification decreased starch in vitro enzymatic digestibility.